Quality Cost Analysis for a Cement Industry: A Case Study - Ayach, Lamiaa; Anouar, Abdellah; Bouziri, Miloud (International Journal of Supply Chain Management, 2018)
In a global competitive market, meeting customers’ requirements is not enough for organizations that are striving for success and welfare. Another goal has to be meet which is the cost challenge .Enterprises need to offer highest quality at the lowest price. To achieve this, organizations must identify potential sources of savings by making an effective control of manufacturing costs. Since quality costs constitute a significant part of these costs, it becomes an imperative for companies to track, quantify and rationalize quality related costs by developing a measurement system adapted to their activities. Most companies, however, are unaware of the quantum of their quality cost and therefore underestimate it. In this context, appears the need to present quality cost as an effective tool of highlighting deficiencies in the system by giving an insight to the huge impact of quality cost on the bottom line as well as on the financial position of the organization. This paper presents a case study conducted in a cement industry that gives awareness and guidance to what requires attention of top management.